Spectral problems with boundary and conjugating conditions depending on a parameter - Komarov, G. N. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We establish generalized orthogonality conditions and prove a theorem on completeness of the collection of eigenfunctions of a spectral problem with boundary and conjugating conditions depending on a parameter for piecewise homogeneous bounded connected and disconnected domains.